175k views
4 votes
Need help finding the limits

Need help finding the limits-example-1
User Mlclm
by
6.8k points

1 Answer

3 votes

Answer:


\displaystyle \lim_(x \to 9) (√(x) - 3)/(9 - x) = (-1)/(6)

General Formulas and Concepts:

Calculus

Limits

Limit Rule [Constant]:
\displaystyle \lim_(x \to c) b = b

Limit Rule [Variable Direct Substitution]:
\displaystyle \lim_(x \to c) x = c

Limit Property [Addition/Subtraction]:
\displaystyle \lim_(x \to c) [f(x) \pm g(x)] = \lim_(x \to c) f(x) \pm \lim_(x \to c) g(x)

L'Hopital's Rule:
\displaystyle \lim_(x \to c) (f(x))/(g(x)) = \lim_(x \to c) (f'(x))/(g'(x))

Differentiation

  • Derivatives
  • Derivative Notation

Derivative Property [Addition/Subtraction]:
\displaystyle (d)/(dx)[f(x) + g(x)] = (d)/(dx)[f(x)] + (d)/(dx)[g(x)]

Basic Power Rule:

  1. f(x) = cxⁿ
  2. f’(x) = c·nxⁿ⁻¹

Explanation:

We are given the following limit:


\displaystyle \lim_(x \to 9) (√(x) - 3)/(9 - x)

Substitute in x = 9 using the limit rule:


\displaystyle \lim_(x \to 9) (√(x) - 3)/(9 - x) = (√(9) - 3)/(9 - 9)

Evaluating this, we have an indeterminate form:


\displaystyle \lim_(x \to 9) (√(x) - 3)/(9 - x) = (0)/(0)

Since we have an indeterminate form, let's use L'Hopital's Rule:


\displaystyle \lim_(x \to 9) (√(x) - 3)/(9 - x) = \lim_(x \to 9) ((1)/(2√(x)))/(-1)

Simplify:


\displaystyle \lim_(x \to 9) (√(x) - 3)/(9 - x) = \lim_(x \to 9) (-1)/(2√(x))

Substitute in x = 9 using the limit rule:


\displaystyle \lim_(x \to 9) (-1)/(2√(x)) = (-1)/(2√(9))

Evaluating this, we get:


\displaystyle \lim_(x \to 9) (-1)/(2√(x)) = (-1)/(6)

And we have our answer.

Topic: AP Calculus AB/BC (Calculus I/I + II)

Unit: Limits

User Mouselangelo
by
5.7k points